Islamic Religious Education Learning Media in the Technology Era: A Systematic Literature Review - Huda, Miftachul; Arif, Muhamad; Rahim, Mohamad Marzuqi Abdul; Anshari, Muhammad (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
Studies on using Islamic religious education instructional media by educators exhibit considerable diversity, with several study findings emerging over the past decade. Notably, incorporating social media platforms such as YouTube and TikTok has been explored to enhance the learning experience. This study aims to achieve two primary goals based on the provided data. There are two main points to consider: firstly, the importance of selecting learning materials for Islamic religious education in the modern age, and secondly, the prevalence of technology-based learning media teachers utilize in Islamic religious education classes. A systematic literature review was employed by searching for results of scientific publications on the global indexation platform (Scopus-Google Scholar) with a period of 2014–2024 by PRISMA analysis. The research results show that the urgency of learning media for Islamic religious education can influence every learning process. Moreover, in the digital era, accessibility and inclusivity are absolute choices that teachers must pay attention to so that every Islamic religious education lesson can run according to the challenges of the times (student needs), be able to increase motivation and influence student learning outcomes. Meanwhile, the distribution of learning media used by Islamic religious education teachers in the technological era is divided into two categories: first, technology-based learning media without an internet network, and second, technology-based learning media with an internet network.